Identifying underlying individuality across running, walking, and handwriting patterns with conditional cycle–consistent generative adversarial networks - Burdack, Johannes; Giesselbach, Sven; Simak, Marvin L.; Ndiaye, Mamadou L.; Marquardt, Christian; Schöllhorn, Wolfgang I. (Frontiers in Bioengineering and Biotechnology, 2023)
In recent years, the analysis of movement patterns has increasingly focused on the individuality of movements. After long speculations about weak individuality, strong individuality is now accepted, and the first situation–dependent fine structures within it are already identified. Methodologically, however, only signals of same movements have been compared so far. The goal of this work is to detect cross-movement commonalities of individual walking, running, and handwriting patterns using data augmentation. 17 healthy adults (35.8 ± 11.1 years, 8 females, 9 males) each performed 627.9 ± 129.0 walking strides, 962.9 ± 182.0 running strides, and 59.25 ± 1.8 handwritings. Using the conditional cycle-consistent generative adversarial network (CycleGAN), conditioned on the participant’s class, a pairwise transformation between the vertical ground reaction force during walking and running and the vertical pen pressure during handwriting was learned in the first step. In the second step, the original data of the respective movements were used to artificially generate the other movement data. In the third step, it was tested whether the artificially generated data could be correctly assigned to a person via classification using a support vector machine trained with original data of the movement. The classification F1–score ranged from 46.8% for handwriting data generated from walking data to 98.9% for walking data generated from running data. Thus, cross–movement individual patterns could be identified. Therefore, the methodology presented in this study may help to enable cross–movement analysis and the artificial generation of larger amounts of data.